Effect of the loss on ignition on the unconfined compressive strength of residual clays from Bogotá-Colombia stabilized with cement (2024)
ABSTRACT: Organic matter in rock aggregates, such as subgrade, sand, and gravel, originates from the decomposition of organic remains, including plants and domestic waste. The method used to measure the organic matter content in aggregates for infrastructure projects is known as Loss on Ignition (LOI) in which the difference in weight before and after calcination is considered the percentage of loss due to oxides, carbon, nitrogen, phosphorus, and sulfur derived from the organic material. This study compares the compressive strength of three clayey wastes sourced from Bogota, ́ Colombia, each with different organic matter contents measured by loss on ignition (LOI), mixed with varying cement contents. A total of 153 cylindrical samples were manufactured using a monotonic compression compaction technique with different cement and water dosages. Monotonic compression is a type of test in which a load is applied continuously from zero until failure occurs, without any unloading. The physical characterization was reviewed with plasticity limits, specific gravity (Gs), methylene blue index (M.B.I.), chemical composition with X-ray Fluorescence (XRF) X-ray diffraction (XRD) and SEM micrographs. Through multivariate statistical techniques, compressive strength was correlated with the Water/Cement ratio and the Cement/Residue ratio, resulting in a function that facilitates calculation of cement dosage and water content. The study identified that the response surfaces of clayey residue types exhibit tighter concavity as organic matter content increases, indicating a narrower range for determining optimum moisture content with higher LOI. This experimental investigation aims to explore the feasibility of incorporating clayey waste enhanced with hydraulic cement into materials for infrastructure construction, thereby reducing reliance on natural resources. However, the results indicate that these materials can be utilized in constructing sustainable pavements by applying more rigorous moisture measurement and control techniques to the mixtures. This approach compensates for the use of waste materials by reducing the need for landfills, saving production energy, preventing pollution from material extraction and exploitation, and decreasing gas emissions that contribute to global climate change.